Reversible photo-induced trap formation in mixed-halide hybrid perovskites for photovoltaics. Issue 1 (11th November 2014) - Hoke, Eric T.; Slotcavage, Daniel J.; Dohner, Emma R.; Bowring, Andrea R.; Karunadasa, Hemamala I.; McGehee, Michael D.
Abstract : A reversible photo-induced instability has been found in mixed-halide photovoltaic perovskites that limits the open circuit voltage in solar cells. Abstract : We report on reversible, light-induced transformations in (CH3 NH3 )Pb(Br x I1− x )3 . Photoluminescence (PL) spectra of these perovskites develop a new, red-shifted peak at 1.68 eV that grows in intensity under constant, 1-sun illumination in less than a minute. This is accompanied by an increase in sub-bandgap absorption at ∼1.7 eV, indicating the formation of luminescent trap states. Light soaking causes a splitting of X-ray diffraction (XRD) peaks, suggesting segregation into two crystalline phases. Surprisingly, these photo-induced changes are fully reversible; the XRD patterns and the PL and absorption spectra revert to their initial states after the materials are left for a few minutes in the dark. We speculate that photoexcitation may cause halide segregation into iodide-rich minority and bromide-enriched majority domains, the former acting as a recombination center trap. This instability may limit achievable voltages from some mixed-halide perovskite solar cells and could have implications for the photostability of halide perovskites used in optoelectronics.